2014
DOI: 10.1371/journal.pone.0111632
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Transport Is Regulated by Its Novel Interacting Partner Rab32

Abstract: Leucine-rich repeat kinase 2 (LRRK2) is a multi-domain 280 kDa protein that is linked to Parkinson's disease (PD). Mutations especially in the GTPase and kinase domains of LRRK2 are the most common causes of heritable PD and are also found in sporadic forms of PD. Although the cellular function of LRRK2 is largely unknown there is increasing evidence that these mutations cause cell death due to autophagic dysfunction and mitochondrial damage. Here, we demonstrate a novel mechanism of LRRK2 binding and transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 67 publications
2
84
0
Order By: Relevance
“…Rab5 was first found to interact with LRRK2 using a yeast-two-hybrid screening approach [71]. Conversely, LRRK2 was identified as an interaction partner in a yeast-two-hybrid screen for Rab32 [72]. High-throughput protein-protein interaction arrays have shown that LRRK2 physically interacts with Rab7L1 (also known as Rab29) [73].…”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rab5 was first found to interact with LRRK2 using a yeast-two-hybrid screening approach [71]. Conversely, LRRK2 was identified as an interaction partner in a yeast-two-hybrid screen for Rab32 [72]. High-throughput protein-protein interaction arrays have shown that LRRK2 physically interacts with Rab7L1 (also known as Rab29) [73].…”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%
“…In addition, LRRK2 was shown to interact with a number of other Rab GTPases, including Rab32 and Rab38 [72]. Recently, phosphoproteomic screens were performed in an effort to identify bona fide LRRK2 kinase substrates [75].…”
Section: A Physiological Role For Lrrk2 At Vesicular Membranesmentioning
confidence: 99%
“…Further studies using cellular and animal models have suggested that the mutant forms of LRRK2 decrease LC3 lipidation and result in the accumulation of autophagic vacuoles (Roosen and Cookson 2016). In addition, LRRK2 was shown to interact with a number of Rab GTPases, including Rab7, Rab32 and Rab38 (Waschbusch et al 2014). Recently, three functionally related genes (DNAJC13, DNAJC6, and GAK) encoding proteins in the evolutionarily conserved Dnaj/Hsp40 protein family have been identified as the PD-related genes (Cardona and Perez-Tur 2016).…”
Section: Membrane Trafficking Defect In Parkinson's Diseasementioning
confidence: 99%
“…It is found in immune cells, in lamina propria macrophages, B-lymphocytes and dendritic cells, and levels are markedly increased in the bowel in CD 320 and in microglia in the nervous system 344 . It interacts with the small GTPases Rab32 and Rab38 with which it co-locates to transport vesicles and recycling endosomes 345 and it is important for the elimination or intracellular Salmonellae 346 and Legionella 347 . Rab32 and Rab38 play an important role in the biogenesis and traffic of melanosomes and lysosomes and this system is disordered in Hermansky-Pudlak syndrome 348 , accounting for the characteristic partial albinism.…”
Section: Lrrk2mentioning
confidence: 99%